Musashi, a trajetória de formação de Miyamoto Musashi durante o exílio - Reis, Bruno Tomaz Custódio dos (2018)
Musashi (1935-1939), Yoshikawa Eiji\'s novel serialized by the newspa-per Asahi Shinbun and considered by John Scott Miller (2009) as a Bild-ungsroman, it narrates from Miyamoto Musashis return from the battle of Sekigahara (1600) to his victory against Sasaki Kojir in Ganry is-land (1612), when he becomes of the best swordsmen at that age. The early seventeenth century Japan that underwent a major transition is the stage for the formation of Musashi in light of the Japanese world and his own feelings and choices. All these changes are intertwined in the decision of self-exile after the seclusion amid the range of erudition, as previously to this watershed, the protagonist himself felt misunder-stood and excluded by his family members and the other members of society. In order to develop this study, we will make a clipping of Mu-sashis path to understand the essence of his isolation, and his choice to preserve his individuality so that it makes it allowed him to exercise his creativity. Thus, based on the panorama on the Bildgunsroman (Ro-mance of Formation) made by Wilma Maas (2000), we will be able to follow the stimuli and aspirations that guides him toward his formation, until reaching a totally unique development. In order to understand Mu-sashi\'s motivation to adopt exile as a way of life, in addition to attesting his gains, we base on the studies of Kat Shichi (2012) and Edward Said (2003).